The Effect of Moringa Seed Filtrate Addition in Tris Citric Egg Yolk Diluent on Brahman Cattle Spermatozoa Quality - Rahmansyah, Arif; Hariani, Dyah (LenteraBio : Berkala Ilmiah Biologi, 2023)
Increased production of Reactive Oxygen Species (ROS) during freezing in liquid nitrogen at a temperature of -1960C causes the plasma membrane of spermatozoa to undergo lipid peroxidation, so it is necessary to add natural antioxidants sources, one of which is Moringa seed filtrate. This study aims to determine the effect of optimal addition of Moringa seed filtrate in Tris Egg Yolk Citrate diluent to maintain the quality of Brahman cattle spermatozoa before and after freezing. The design of this study was a completely randomized design with 5 treatments and 4 repetitions, namely P0 (Without Addition of Moringa seed filtrate); P1 (Addition of 1.5% Moringa seed filtrate); P2 (Addition of 3.0% Moringa seed filtrate); P3 (Addition of 4.5% Moringa seed filtrate); and P4 (Addition of 6.0% Moringa seed filtrate). The parameters measured were spermatozoa motility based on individual movements, viability based on the number of live spermatozoa with eosin-negrosin staining, and membrane integrity based on the number of spermatozoa with intact membranes (straight tails) using the Hypoosmotic Swelling Test. The data were tested for normality using the Kolmogorov-Smirnov, one-way ANOVA, and Duncan’s. The results showed a significant effect of giving FBK in TKTS diluent on the sperm quality of Brahman cattle (P<0.01). The addition of 4.5% FBK resulted in optimal spermatozoa motility after freezing of 35,75 ± 3,27%, optimal viability of 57.75±0.43%; and the optimal membrane integrity of 53.75±0.43%. Based on the study’s results, it can be concluded that adding 4.5% FBK in TKTS diluent is the optimal dose.